Haunted Washington : ghosts and strange phenomena of the Evergreen State - Stansfield, Charles A. (Stackpole Books, 2011)
From the Cascades to Puget Sound and the Olympic Peninsula, the Evergreen State has a rich and varied paranormal past. Here you'll find the most notorious Bigfoot sightings, UFO reports, and strange occurrences at Grand Coulee Dam, Olympic National Park, and Fort Vancouver.